2018
DOI: 10.1308/rcsann.2018.0172
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic yield of computed tomography in the management of acute flank pain and the emergency intervention rate for a proven acute ureteric stone

Abstract: Introduction The diagnostic and management pathways for patients presenting with acute flank pain are complex. Although computed tomography (CT) of the kidneys, ureters and bladder (KUB) is the gold standard investigation for urolithiasis, the multitude of differential diagnoses must also be considered in the context of long-term risk from ionising radiation. This study investigated the integrated role and diagnostic yield of non-contrast CT in cases of acute flank pain. Methods A retrospective cohort study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…We found that ultrasound has a high positive rate for ureteral stone detection in 79% of the cases, although detection of ureteral stones less than 5mm in size was 70%. Ultrasound revealed a false negative in stone locations for ureterovesical junction [19] , 14 in distal ureteral stone, six in the mid ureter, and three in the upper ureter.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…We found that ultrasound has a high positive rate for ureteral stone detection in 79% of the cases, although detection of ureteral stones less than 5mm in size was 70%. Ultrasound revealed a false negative in stone locations for ureterovesical junction [19] , 14 in distal ureteral stone, six in the mid ureter, and three in the upper ureter.…”
Section: Resultsmentioning
confidence: 95%
“…Female patients are at the highest risk for developing solid cancer from exposure to ionizing radiation [19] . Ultrasound investigation for flank pain may be relevant to minimize radiation risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advancements have introduced low-dose NCCT scanning protocols for detecting urolithiasis/nephrolithiasis, balancing diagnostic efficacy with reduced radiation exposure (8,9). Given the high sensitivity and specificity of NCCT-reported to be between 95-98% and 96-100%, respectively-our hypothesis is that NCCT can accurately detect and measure stones that may be missed by IVP in patients presenting with urolithiasis symptoms (10). This study aims to address the limitations of IVP by using NCCT to accurately diagnose urolithiasis/nephrolithiasis in symptomatic patients who had negative IVP results.…”
Section: Introductionmentioning
confidence: 99%